Search Frictions, Credit Constraints and Firm Financed General Training - Christian Holzner (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
This paper shows that in a search model where future employers of trained workers donot benefit from the training in other firms, investment into general training will only be below the competitive level if workers are credit constrained. If workers are credit constrained, then the training firm cannot recover the cost of training since trained workers will search for a better paid job. This does, however, not imply that trainees will benefit from training. Only if the trainee wage is bounded by the workers' credit constraints do trainees gain from training.
Keywords: J24; J31; J41; J63; 330; General training; credit constraints; search frictions; matching